Jejak Aroma Kopi Arabika di Massenrempulu 1970-2016 - Ismail Muslimin; Ahmadin Ahmadin; Patahuddin Patahuddin (PATTINGALLOANG, 2017)
This study aims to determine the background of coffee farming, coffee agriculture development to agricultural impacts of Arabica Coffee in Benteng Village Alla Utara District Baroko. This type of research is qualitative research. This research is done through interview and literature study using historical method through several stages: heuristic (source collection), source critic, interpretation, and historiography. The results showed that the existence of Arabica Coffee farm in Benteng North Alla Village began in 1750 after the Dutch managed to colonize the North Alla Fort Village. The development of coffee plantations began to be re-enacted when the arrival of Ir. Sugiyo from Jember, East Java. Ir. Sugiyo is an agricultural employee from Java. Ir. Sugiyo introduced a kind of Arabica Coffee that has good quality. Based on the result of the research, it can be concluded that Arabica Coffee has an impact to the society economy in Benteng Alla Utara village which is providing employment such as season laborer and day laborer, ownership of property for Arabica coffee farmer, and giving impact to regional income.